2016
DOI: 10.3126/njdvl.v12i1.10595
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Of Skin Diseases In A Rural Village Development Community Of Nepal

Abstract: CitationShrestha R, Lama L, Gurung D, Shrestha DP, Rosdahl I. Pattern of skin diseases in a rural village development community of Nepal. NJDVL 2014; 12(1): 41 -44. AbstractIntroduction: Skin diseases are a common cause of morbidity in Nepal as per the health services report. There is limited information on the prevalence and pattern of skin diseases in the community.Objectives: This study was conducted to determine the pattern of skin diseases in a rural village development community of Nepal. Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
4
9
0
Order By: Relevance
“…Shrestha R. et al had done study on pattern of skin diseases in a rural area of Nepal and found that eczema was the commonest dermatoses. 4 Similar results were in others studies as well. [6][7][8][9][10] But study done by Poudyal Y. et al showed dermatophytes was the commonest skin disease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Shrestha R. et al had done study on pattern of skin diseases in a rural area of Nepal and found that eczema was the commonest dermatoses. 4 Similar results were in others studies as well. [6][7][8][9][10] But study done by Poudyal Y. et al showed dermatophytes was the commonest skin disease.…”
Section: Discussionsupporting
confidence: 88%
“…4 Similar results were in others studies as well. [6][7][8][9][10] But study done by Poudyal Y. et al showed dermatophytes was the commonest skin disease. 11 However, it was the second common disease in our study (16.68%) which was comparable in both gender.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, most of these studies are confi ned to Terai and Hilly regions of Nepal. In one of the studies conducted by Shrestha R et al 8 in rural village development community of hilly region of Nepal, the camp prevalence of skin diseases was 83% with eczema (36.4%), followed by infec ons (28.4 %), acne (22%), Pigment disorders (34%), and Ur caria (12.3%). In another similar study in Terai region by Walker SL et al 3 , the point prevalence of skin disease in camp was 62.2% with dermatophyte infec ons (11.4%) being the commonest followed by P. versicolor (8.9%), Acne( 7.7%), Melasma (6.8%), eczemas 5.6%) and P. alba (5.2%).…”
Section: Discussionmentioning
confidence: 97%
“…8 A community-based study reported that skin disorders are common (20.1% of the surveyed population) and eczema was the most common dermatosis (28.1%) diagnosed. 9 The rate of asthma increases as communities adopt western lifestyles and become urbanised. Kathmandu is rapidly urbanising with a high level of pollution 10 and is therefore at risk of a rapid increase in asthma prevalence paralleled by other allergic disorders.…”
Section: Introductionmentioning
confidence: 99%